Land drainage and flood defence delegate information : Monday 1 December 1997 : a joint initiative of Thomas Telford Conferences and the Boards of the Institution of Civil Engineers. (Thomas Telford, 1997)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in December 1997.
Keywords: Drainage -- Congresses.; Flood control -- Congresses.; elektronické knihy; electronic books